Error And Remedial Work Of Comparative And Superlative Adjective At Dhyana Pura University - Wardhana, I Gede Neil Prajamukti; Sari, Ni Putu Sintya Puspita; Dewi, Ni Luh Desy Suari (International Journal of Linguistics and Discourse Analytics, 2024)
This analysis discussed about Error analysis and remedial work on 4th semester students at Dhyana Pura University Bali in the year of 2023/2024 odd semester. This results of the material of comparative and superlative adjective given to 4th semester students from five different study programs namely (English literature, Psychology, Accountant, Management, D3 Digital Marketing) with the total 16 students. The purpose of this study was to find Error and find the most efficient way of giving the remedial task for in-depth understanding. This study uses qualitative research methods with descriptive research types to provide an explanation for the mistakes the students made in the students’ tasks. The data collection technique used by the author is through the results of the first error test and providing material in the form of remedial work that uses questions that are easier than the first test questions. Using the types of error theory from Dulay 1982, this analysis found that the types of errors produced by the 4th semester students studied, reflect the types of error namely omission, addition, mis formation, and mis ordering forms